2002
DOI: 10.1177/1097184x02004003004
|View full text |Cite
|
Sign up to set email alerts
|

Puerto Rican Men and the Struggle for Place in the United States

Abstract: This article explores the construction of masculinity among poor and working-class Puerto Rican men on the mainland, filling a distinct gap in both the literatures on Puerto Ricans' and men's studies. Based on extensive interviews with a group of Puerto Rican men, the authors focus on the ways in which these men are staking out their identity on the mainland, as well as the social context in which this identity construction is taking place. It is argued that an affirmation of cultural citizenship is wrapped ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…These factors may impede foreign-born Latinos from developing their role as the provider and obtaining the opportunity to economically support a large household. Latinos' limited economic opportunity coexists with the increased economic independence of foreign-born Latinas in the U.S., which further challenges the provider role of the hegemonic "macho" (Torres, 1998;Weis, Centrie, Valentin-Juarbe, & Fine, 2002).…”
Section: The Increase Of Vasectomies Reported In the Document Currentmentioning
confidence: 99%
See 1 more Smart Citation
“…These factors may impede foreign-born Latinos from developing their role as the provider and obtaining the opportunity to economically support a large household. Latinos' limited economic opportunity coexists with the increased economic independence of foreign-born Latinas in the U.S., which further challenges the provider role of the hegemonic "macho" (Torres, 1998;Weis, Centrie, Valentin-Juarbe, & Fine, 2002).…”
Section: The Increase Of Vasectomies Reported In the Document Currentmentioning
confidence: 99%
“…Feminist anthropologist Rayna Reiter argues that the earliest societies were egalitarian, but male dominance began to develop with the roles of male-hunter and female-mothering, arranged marriages (where women were exchanged for goods), and the reproductive representations that many times differ from traditional ideas of family size, gender roles, birth control utilization, and masculinity (Maternowska, Withers, & Brindis, 2014). In Latin America, for example, hegemonic masculinity traits support the role of male authority, but in the U.S. male authority may be questioned since this society is considered to be more egalitarian (Donaldson, Hibbins, Howson, 2009;Maternowska et al, 2014;Torres, 1998;Weis et al, 2002). According to Hondagelu-Sotelo, "…Mexican male immigrants in the United States found that their patriarchal privileges were significantly diminished in the process of migration" (Donaldson et al, 2009, p. 80).…”
Section: Introductionmentioning
confidence: 99%